Indian chiefs and colonial agents in the mission of San Pablo de Río Bueno (1777-1820): expansion, conflict, and negotiation - Yasima, C.; Urbina A, S.; Adán A, L. (Universidad Catolica del Norte, 2022)
Beginning with From the analysis of the baptism and marriage records of Indians from the San Pablo of Río Bueno mission, the social relations contracted by Indian chiefs and officials are studied. The hegemony achieved by Indian officials in establishing social and political ties with the indigenous people of the Llanos de Río Bueno and the integration of several caciques from the jurisdiction of Valdivia and Osorno cities into the colonial order is highlighted. All this in a context of expansion and settlement of colonial power, where, although the construction of agreements with the indigenous authorities prevailed, it was war that consolidated in 1792 and 1793 almost half a century of Hispanic expansion on the Forntera de Arriba or “upper borderland” of the Kingdom of Chile.
Caciques y funcionarios de indios en la misión de San Pablo de Río Bueno (1777-1820): Expansión, conflicto y negociación
Keywords: Humanities; Political science; Art; https://purl.org/pe-repo/ocde/ford#6.00.00